Application and Use of Rhetoric in the Scientific Field of Civic Education - Ari Hudrianto; Samsuri; Suyato (ASTEEC, 2023)
Studying rhetoric means discussing the concept and application of a philosophy of science in a particular scientific field. The philosophy of science is all human thoughts spontaneously respond to every problem in the context of the basic concept of the formation of a science or the relationship between one science and another for the good of mankind In this method to be able to study rhetoric as a use and application in the scientific field of civic education we can use literature study or literature study. A systematic scientific method of literature. In the explanation above, the application of rhetoric in the scientific field of civic education is a form of branch of science that aims to form good and smart citizenship in civic life. So in the delivery of civic education science in delivering learning material can be done by providing logical arguments by showing evidence directly or indirectly to be able to prove scientific Civic education application of rhetoric in scientific midwives Civic education is a branch of the discipline of law and politics packaged in education which aims to form Smart and Good Citizenship. With good, ethical, and emotional delivery supported by the delivery of strong and accurate evidence, and can argue logically in presenting the evidence.